Monodromy in Dicke superradiance. (6th July 2017) - Kloc, Michal; Stránský, Pavel; Cejnar, Pavel
Abstract: We study the focus–focus type of monodromy in an integrable version of the Dicke model. Classical orbits forming a pinched torus represent analogues of the dynamic superradiance under conditions of a closed system. Quantum signatures of monodromy appear in lattices of expectation values of various quantities in the Hamiltonian eigenstates and are related to an excited-state quantum phase transition. We demonstrate the breakdown of these structures with an increasing strength of non-integrable perturbation.